STUDY OF OBSERVATION FLUORESCENCE WITH DOMAIN WAVELENGTH BASED ON SPECTROSCOPY FLOURESCENCE FOR MATERIAL IDENTIFICATION - Ainun Mardiyah Lubis; Bisman Perangin – angin; Nasruddin (AGRIUM: Jurnal Ilmu Pertanian, 2016)
A research on the Study of Observation Fluorescence with  Domain Wavelength Based on Spectroscopy Flouresensi for Material Identification. The sample at this object are olive oil, sandalwood oil, and cem-ceman oil, the result of measurement for olive oil, obtained energy absorption (E1) and excitation energy (E2) respectively each 0,388 . 10 -18 Joule dan 0,383 . 10 -18 Joule, the wavelength of absorption (λ1) and the excitation wavelength (λ2)  each amounting to 512 nm and 518 nm absorption intensity (I1) and Fluorescence Intensity (I2) each amounting to 76 and 73. For Sandalwood oil, gained energy absorption ( E1) and excitation energy (E2) respectively  each  0,360 . 10 -18 Joule dan 0,357 . 10 -18 Joule, the wavelength of absorption (λ1) and the excitation wavelength (λ2)  each amounting to 552 nm and 557 nm, the absorption intensity (I1) and Fluorescence Intensity (I2)  each amounting to 42 and 41. For cem - ceman oil, gained energy absorption (E1) and excitation energy (E2) respectively  each  0,39 . 10 -18 Joule and 0,386 . 10 -18 Joule, the wavelength of absorption (λ1) and the excitation wavelength (λ2)  each amounting to 510 nm and 514 nm  absorption intensity (I1) and Fluorescence Intensity (I2)  each 45 and 43. . Measurements were made with a detector ( Ocean Optics USB HR2000 ) .Keywords : fluorescence, wavelength specktrum, detector, essential oils, olea europia.l